Intellectual Capital Disclosure and Its Impact on the Value of Companies in Emerging Market - БайбуринаЭльвина Рифхатовна; ГребцоваЕлена Геннадьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
Authors: Elvina Rifhatovna Bayburina National Research University The Higher School of Economics Elena Gennadyevna Grebtsova National Research University The Higher School of Economics The development of information technologies, increase of the knowledge significance, the vital importance of innovation as the tool to obtain the competitive advantage issue new and complex challenges to modern companies in many aspects of their business. One of such issues is the adequate information disclosure about the intellectual capital of the company to satisfy the inside and outside stakeholders, such as: management of the company, its’ employees, investors, government, credit institutions and many others. It is necessary to note that information disclosure is particularly relevant to companies in emerging markets due to their inefficiency, which often leads to inadequate assessment by stakeholders. This paper presents the non-financial evaluation of the intellectual capital disclosure by the cumulative method (intellectual capital disclosure index). This index is used as the fundamentally different analytical tool to investigate the information disclosure of intellectual capital by the means of empirical panel data analysis, in order to evaluate the systematical contribution of intellectual capital into value creation of the companies of the largest developing countries. The paper is organized as follows: in the first part it provides a brief academic overview of the definitions and classifications of intellectual capital, methods of evaluation. The intellectual capital impact on the value of companies is also briefly discussed in this part of the paper. The index regression model of the impact of intellectual capital disclosure on the value is discussed in the second part of the paper. Finally, main results and conclusions of the research and recommendations for further development of the topic are presented. The study describes the disclosure of information on intellectual capital of the companies in emerging markets (Brazil, Russia, China, South Africa), the main finding is that the disclosure of such information contributes to the growth of the value of the company, because it allows stakeholders to evaluate it adequately. The key results of the project “Researches of corporate financial decisions of the companies of Russia and other countries with emerging capital markets under conditions of global transformation of the capital markets and formation of economy of innovative type”, carried out within the framework of the Programme of Fundamental Studies of The National Research University “Higher School of Economics” in 2012, are presented in this paper.